Permissible constitutional requirements for the enforcement of public liability after the repeal of the law establishing it (on the example of liability for failure to submit calculation of social insurance fee) - Sergey D. Knyazev (Правоприменение, 2019)
The subject of the paper is temporal effect of abolition of the law establishing liability (especially liability for failure to submit calculation of social insurance fee).The main aim of the paper is to confirm or disprove the hypothesis that the application of the rule of liability after its repeal depends on whether the law has introduced a rule on a similar offense and what is its objective side. The author wants to apply this hypothesis to the Russian legislation concerning liability for failure to submit calculation of social insurance fee.The description of methodology. The author uses economic approach and the theory of rational choice as well as the dialectic and formal‐legal methodology. The author uses general scientific methods (analysis, synthesis, description) as well as particular academic legal methods (formal‐legal method, interpretation of legal acts.The main results and scope of their application. Temporal rules have universal general legal value, they must be applied to all types of legal liability. The repeal of the law establishing liability blocks generally the possibility of applying such law in the future. When the repeal of a law providing for liability for a specific offence is accompanied by the adoption of another law on liability, it does not entail the cancellation, but strengthening or mitigation of liability. If the repeal of the law establishing liability is intended to "transform" the legal (sectoral) nature of liability, it is permissible to apply the revoked law to persons who have committed the offence according to this law before its cancellation. The adoption of a law that mitigates liability requires its extension to those who have committed the relevant unlawful act before the new law is introduced. The legal rules abolishing one type of liability for a particular offence and establishing a more or less strict liability of another type should enter into force simultaneously, without any time gap. Otherwise the repeal of the law establishing liability would undoubtedly "nullify" the possibility of holding someone liable for the relevant offence that occurred prior to the repeal.According to pt. 1 of art. 119 of the Russian Tax Code failure to submit the calculation of social insurance fees constitutes an offense only if these contributions themselves were not paid in full in a timely manner. After the Federal law "On social insurance fees… " have been revoked since January, 1, 2017 the failure of the payer of social insurance fees to submit the calculation of accrued and paid insurance fees ceased to be considered by the legislator as an offense. Ergo since that date holding someone (who had already paid social insurance fee) to responsibility for non‐submitting the calculation shall be completely excluded. The results of research may be used as the basis of correction of temporal rules in any legal system to make enforcement more just.Conclusions. The author confirmed the hypothesis that the application of the rule of liability after its repeal depends on whether the law has introduced a rule on a similar offense and what is its objective side. After the cancellation of Federal law "On social insurance fees...", the article of the Russian Tax Code replaced this law does not provide for liability for failure to submit calculation, when payment of the social insurance fee was made on time. And persons who did so cannot take any legal responsibility.